2021
DOI: 10.1037/drm0000165
|View full text |Cite
|
Sign up to set email alerts
|

Dream sharing and the enhancement of empathy: Theoretical and applied implications.

Abstract: This study replicated and extended a previous finding that the discussion of dreams increases the level of empathy toward the dreamer from those with whom the dream is discussed. The study addressed mediating variables for the empathy effect. Participants were recruited in dyads who already knew each other and were assigned dream-sharer and discusser roles.Each dyad used the Ullman dream appreciation technique to explore the relationship of the sharer's dreams to recent experiences in the sharer's life, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…For instance, Askari et al (2022) found that UEDGA sessions promoted exploratory insights, action‐oriented reflections and experiential learning in healthy women, highlighting its effectiveness in facilitating personal growth and insight among the non‐clinical population, particularly females. Furthermore, empirical evidence from Blagrove et al (2021) supports the notion that dream sharing within a group enhances empathy, strengthens bonds and provides support between the dreamer and group members. In addition, Shaw's study (Shaw, 2021) revealed that participants engaged in UEDGA sessions reported improvements in creativity.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, Askari et al (2022) found that UEDGA sessions promoted exploratory insights, action‐oriented reflections and experiential learning in healthy women, highlighting its effectiveness in facilitating personal growth and insight among the non‐clinical population, particularly females. Furthermore, empirical evidence from Blagrove et al (2021) supports the notion that dream sharing within a group enhances empathy, strengthens bonds and provides support between the dreamer and group members. In addition, Shaw's study (Shaw, 2021) revealed that participants engaged in UEDGA sessions reported improvements in creativity.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast to these theories of within-sleep functions of dreaming, Blagrove at al. (2019bBlagrove at al. ( , 2021 have proposed that dreams have an adaptive function at the point of being told to others, in that they enhance empathy between the dream-sharer and those with whom the dream is told and discussed.…”
Section: I J O Rmentioning
confidence: 99%
“…Given the above issues, Blagrove et al (2019bBlagrove et al ( , 2021 proposed that functional and evolutionarily adaptive consequences of dream content could instead occur after sleep, as a result of the sharing of dreams, such sharing taking advantage of the long REM periods that occur for biological reasons near the end of the night. Phylogenetically, dreaming might have originated from memory consolidation or threat rehearsal or other functions, in early humans and other animals, or indeed might be no more than a spandrel, an epiphenomenon of sleep (Flanagan, 2000): the theory proposed here is that when dream-sharing started, new selective pressures began for the dream content.…”
Section: Critique Of Proposed Within-sleep Functions Of Dreamsmentioning
confidence: 99%
See 2 more Smart Citations